The Role of K+ Channel Subtypes in Catechin Induced Vasorelaxation in Rat’s Aortic Rings. - Omar A. M. Al-Habib; Fakhir N. K. Sabir (Science Journal of University of Zakho, 2015)
The current study aimed to investigate the role of K+ channels subtypes in relaxant effects of catechin on rat’s aortic rings. The isometric tension of the thoracic aorta was measured using ADI PowerLab Data Acquisition System.  Catechin at concentrations (10-5 to 5x10-1M) produced more potent relaxant effects in phenylephrine (10-6 M)  precontracted aortic smooth muscle  with Log IC50’s of -1.159 mg/ml as compared to potassium chloride (60 mM) with Log IC50’s of -6.373  mg/ml . The catechin induced relaxation in aortic rings precontracted with phenylephrine was 17.464 ± 0.068 %, where as for  aortic rings precontracted with potassium was only 5.574 ± 0.131%.  In aortic rings preincubated with glibenclamide (10-5M) and tetraethylammonium (1mM), catechin  relaxant effect was enhanced with Log IC50s of -3.119 and -3.001 mg/ml, respectively. On the other hand, in aortic rings precontracted with PE and preincubated with BaCl2 and 4-AP, catechin induced    statistically non-significant relaxant effects as compared with aortic rings of the control aortic ring  which was precontracted with PE. From the results of the current study, it can be concluded that catechin produced more potent vasorelaxant effect on aortic rings preincubated with phenylephrine that KCl. This vasorelaxant effect of catechin is produced via the activation of  both KATP and Kca, but not Kir and Kv channels subtypes.